A STUDY OF THE EFFICIENCY OF CULTURE MEDIA FOR THE RECOVERY OF LYOPHILIZED PATHOGENIC BACTERIA - V. Ushkalov; L. M. VYGOVSKA; A. V. USHKALOV; Serhii Boianovskyi; A. V. HRANAT; S. A. TERESHCHENKO; L. O. DAVYDOVSKA; Y. Y. VISHOVAN (Ukrainian Journal of Veterinary Sciences, 2021)
Today, the most appropriate way of long-term storage of most microorganism strains in collections is their lyophilization. The rate and quality of the recovery of biological properties in lyophilized bacterial cultures depend on the quality of culture media used for this purpose. The purpose of this study was to investigate the effectiveness of culture media for the recovery of lyophilized pathogenic bacteria. The strains of Salmonella typhimurium, Pasteurella multocida, Yersinia pseudotuberculosis, and Staphylococcus aureus from the collection of the Ukrainian Laboratory of Quality and Safety of Agricultural Products of the National University of Life and Environmental Sciences of Ukraine were used in the study. In order to restore lyophilized bacterial cultures, several variants of culture media were used: meat-peptone broth (Pharmactive, Ukraine) with the addition of 5% equine serum and 0.5% glucose; meat-peptone broth (Pharmactive, Ukraine) with the addition of 5% bovine serum and 0.5% glucose; meat-peptone broth (Pharmactive, Ukraine) with the addition of 5% bovine serum and 0.5% glucose; brain-heart infusion broth (HiMedia, India) and tryptone soya broth (HiMedia, India). Faibich protective medium was used as a cryoprotectant. It was found that in the process of sublimation and cryopreservation of cultures of Salmonella typhimurium, Pasteurella multocida, Yersinia pseudotuberculosis, and Staphylococcus aureus, the loss of viable microbial cells was 99.91-99.98%. The concentration of viable microbial cells in lyophilized cultures of Salmonella typhimurium, Pasteurella multocida,Yersinia pseudotuberculosis, Staphylococcus aureus was recorded in the range of 1.4 × 104-1.7 × 106 CFU/cm3. During a single passage on different culture media, obtained biomass of the studied cultures was in the initial titer x × 109. The highest productivity in recovered cultures was obtained using brain-heart infusion broth manufactured by HiMedia, India (concentration of live microbial cells in experimental cultures was recorded in the range of 5.7-6.4 × 109 CFU/cm3)